MANG@COAST: A spatio-temporal modeling approach of muddy shoreline mobility based on mangrove monitoring - Augusseau, P.E.; Proisy, C.; Gardel, A.; Brunier, G.; Granjon, L.; Maury, T.; Mury, A.; Staquet, A.; Santos, V.F.; Walcker, R.; Degenne, P.; Lo Seen, D.; et al. (Environmental modelling & software : with environment data news, 2025)
Highly dynamic wave-exposed muddy coasts harbouring mangrove ecosystems can be subject to both marked accretion and erosion depending on the complex interactions between mud and waves. We propose a multiscale modelling approach and empirical equations calibrated and integrated into a landscape dynamics model implemented on a mud-bank coast using the Ocelet language to simplify the complex processes driving sea-mangrove coastline dynamics and quantity them with 10 years of satellite observations of mangrove shoreline fluctuations. We find that fluctuations in seafront mangroves can be simulated with acceptable accuracy along 200 km of coastline. In the absence of mud banks, seasonal wave forcing resulted in erosion rates reaching 1100 m/y. Our findings indicate that wave energy can be reduced by 90% at all locations when the width of mud banks exceeds 2000 m in front of the mangroves. Finally, we discuss the potential of this modeling approach for anticipating coastal changes. [Display omitted] •MANG@COAST simulates mangrove fluctuations on the muddy French Guiana coast.•MANG@COAST is calibrated with satellite observations covering 10 years and a coastline of 200 km.•The model quantifies the critical role of mud banks in attenuating waves and protecting mangroves.•Mangrove ability to expand is a key process in modeling coastal changes.